Meter in Music, 1600-1800: Performance, Perception, and Notation - Houle, George (Bloomington, IN Indiana University Press, 2000)
A Choice Outstanding Academic Book of 1988All practising musicians with an interest in the baroque owe it to themselves to be exposed to the ideas contained in this book. ContinuoThis is a book from an excellent musician in the early field who turns out also to be a most persistent scholar . . . Early Music . . . the book offers a vast quantity of data from a wide range of sources. . . . George Houle is to be congratulated for his honest presentation of the entire spectrum. Music Educators JournalThe treatment of meter in performance has evolved dramatically since 1600. Here is a practical guide for the performer, with many quotations from early manuals and treatises, and abundant examples.
Introduction -- 1. The Origins of the Measure in the Seventeenth Century -- 2. Time Signatures in the Eighteenth Century -- 3. Rhythmopoeia: Quantitative Meters in Poetry and Music -- 4. Quantitas Intrinseca: The Perception of Meter -- 5. Articulation of Quantitative Meter -- 6. Accent as Measure Articulation and as Measure Definition -- Appendix: Rhythmopoeia according to Johann Mattheson and Wolfgang Caspar Printz
Includes a bibliography and index
Keywords: Mattheson, Johann -- 1681-1764; Printz, Wolfgang Caspar -- 1641-1717; 17th Century (1601-1700); 18th Century (1701-1800); Meter; Music theory; Musical analysis